(untitled) (American Journal of Islam and Society, 2006)
This extensive survey of the Kurds’ history is divided into five sections: “The Kurds in the Age of Tribe and Empire,” “Incorporating the Kurds,” “Ethno-nationalism in Iran,” “Ethno-nationalism in Iraq,” and “Ethnonationalism in Turkey.” An introduction on Kurdish identity and social formation, as well as four appendices discussing the Treaty of Sèvres and the Kurds of Syria, Lebanon, and Caucasia, are also included. David McDowall, a noted British specialist on Middle Eastern minority affairs and an acknowledged expert on Kurdish studies, has extensively revised the 1996 second edition of his book. He provides an analysis of recent Kurdish events and a more up-to-date bibliography at the end of each section. This highly detailed history begins in the nineteenth century and ends in the present day. The author discusses the interplay of the old and new facets of Kurdish politics: local rivalries within Kurdish society; the enduring authority of the traditional leadership represented by sheikhs and aghas; the failure of modern nation states to respond to the challenge of Kurdish nationalism; and the use of Kurdish groups as pawns by major western powers and regional states in the region’s power politics. His methodology is primarily political-historical in nature; however, anthropological and social analysis are not totally lacking. As presented by McDowall, a close scrutiny of modern Kurdish history reveals striking continuities. For example, one pattern has characterized Kurdish-Iraqi relations since 1958: Each Iraqi government pursued peace negotiations with the Kurds at first, only to fight them when it felt secure about its rule. This pattern is also found in Iran’s relations with its Kurds. Turkey, however, has pursued a policy that seeks to assimilate and, at times, even ethnically cleanse its Kurdish population. There is also continuity in the major powers’ manipulation of the “Kurdish card” in Iraq. McDowall writes that in 1976, the Select Intelligence Committee of the House of Representatives reported to the House that neither Iran nor the United States would like to see the civil war going on in Iraq at that time resolved in a way that would give the Kurds a clear win. Twenty years later, in 1991, the United States implemented a similar policy with the Kurds’ so-called “exclusionary zone’’ in northern Iraq. Fearing the consequences likely to follow Saddam Hussein’s overthrow – in particular, the dismemberment of Iraq and wider regional instability – the United States refused to give the Kurds sufficient aid to enable them to establish an independent homeland ...